Declining trends of polychlorinated dibenzo-p-dioxins, dibenzofurans and non-ortho PCBs in Canadian Arctic seabirds. (January 2017) - Braune, Birgit M.; Mallory, Mark L.
Abstract: Polychorinated dibenzo- p -dioxins (PCDDs), polychlorinated dibenzofurans (PCDFs) and dioxin-like polychlorinated biphenyls (PCBs) such as the non- ortho PCBs (nPCBs) persist in the environment despite international measures to ban their emissions. We determined congener patterns and temporal trends for PCDDs, PCDFs, nPCBs as well as their toxic equivalents (TEQs) in eggs of thick-billed murres ( Uria lomvia ) and northern fulmars ( Fulmarus glacialis ) sampled from Prince Leopold Island in the Canadian Arctic between 1975 and 2014. The dominant PCDD congeners were 1, 2, 3, 7, 8-PnCDD, 2, 3, 7, 8-TCDD and 1, 2, 3, 6, 7, 8-HxCDD, and the dominant PCDF congener was 2, 3, 4, 7, 8-PnCDF. The nPCB profile was dominated by PCB-126. The TEQ profile in the murre eggs was dominated by nPCB-TEQ whereas in the fulmar eggs, the PCDF-TEQ contribution to ΣTEQ was slightly greater than that of nPCB-TEQ. Concentrations of ΣPCDD, ΣPCDF, ΣnPCB and ΣTEQ declined between 1975 and 2014 in both murre and fulmar eggs. Based on TEQ thresholds in the literature for other species, and taking into account the trend towards declining TEQ levels, it is unlikely that current levels of PCDDs, PCDFs or nPCBs are affecting the reproductive success of thick-billed murres or northern fulmars in the Canadian Arctic. Graphical abstract: Declining trends of polychlorinated dibenzo- p -dioxins, dibenzofurans and non- ortho PCBs in Canadian Arctic seabirds. Highlights: PCDDs, PCDFs and non- ortho PCBs were measured in seabird eggs from Canada's Arctic. ΣPCDD, ΣPCDF and ΣnPCB declined from 1975 to 2014 in murre and fulmar eggs. Toxic equivalents (TEQs) also declined in murre and fulmar eggs from 1975 to 2014. The major PCDD/F congener was 2, 3, 4, 7, 8-PnCDF; PCB-126 was the main nPCB congener. nPCB-TEQ, and PCDF-TEQ in fulmar eggs, were major contributors to the TEQ profile. Abstract : Declining trends of dioxins, furans and non- ortho PCBs in seabird eggs from the Canadian Arctic.